Price Volatility and Marketing Efficiency of Chili Pepper (Capsicum annuum L.): a Farmer share Approach in Pagar Alam City - Serly Novita Sari; Aisah Aisah; Sri Indaryati (Universitas Muhammadiyah Palembang, 2026)
Chili price fluctuations have become one of the major issues in the horticultural marketing system because they affect farmers’ income stability and consumers’ purchasing power. The considerable price differences between producer and consumer levels indicate the existence of price disparities and marketing margins that potentially reduce the efficiency of chili distribution. This study aims to analyze the dynamics of producer and consumer chili prices and to measure Farmer share as an indicator of chili marketing efficiency in Pagar Alam City in 2025. The study employed a quantitative descriptive method using secondary data on producer prices and retail prices obtained from the Department of Agriculture of Pagar Alam City. The analysis focused on curly red chili, large red chili, and cayenne pepper using Farmer share and marketing margin approaches. The results showed that chili prices experienced significant fluctuations throughout 2025. Cayenne pepper had the highest price volatility, while curly red chili recorded the highest marketing margin during certain periods. In general, the Farmer share values of all chili commodities were above 60%, indicating that the marketing system was relatively efficient. However, in several months, increased marketing margins reduced the proportion of prices received by farmers. Price fluctuations were influenced by seasonal changes, market supply, distribution costs, and the length of the marketing chain. High marketing margins indicate that chili distribution has not been fully efficient. Therefore, strengthening farmer institutions, developing digital marketing systems, and providing real-time price information are necessary to improve Farmer share and the welfare of chili farmers.